Biocompatible pectin-based hybrid hydrogels for tissue engineering applications. (22nd November 2021) - Tortorella, Silvia; Inzalaco, Giovanni; Dapporto, Francesca; Maturi, Mirko; Sambri, Letizia; Vetri Buratti, Veronica; Chiariello, Mario; Comes Franchini, Mauro; Locatelli, Erica
Abstract : Hybrid hydrogels made of chemically modified pectin, gelatin and xanthan gum have been formulated and processed through a double crosslinking step, aimed at wound healing applications. Abstract : Hybrid hydrogels made of chemically modified pectin, gelatin and xanthan gum have been formulated and processed through a double crosslinking step, aimed at wound healing applications. The formulation of hybrid hydrogels finds its cornerstone in the possibility to create a supportive environment for cell adhesion and proliferation, ensuring the transport of nutrients via porous structures, together with mechanical properties closely comparable to the native tissue. The hydrogels present a good swelling behavior, resistance to dissolution and fragmentation in simulated biological environment (PBS 1× and DMEM) for up to 20 days and the porous structure, as pictured via scanning electron microscopy, has been foreseen to help cell migration and the exchange of biomolecules. Rheological characterization showed desired mechanical features, while the biocompatibility has been assessed via live/dead assay on murine fibroblasts. Finally, the hybrid hydrogels have also been proved suitable for mechanical extrusion, demonstrating the possibility of cell encapsulation in the future perspective of 3D bioprinting applications.